Mencermati Rancangan Undang-undang Pengadaan Barang dan Jasa Pemerintah - Adi Susila (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2012)
The management of Goods and Services Procurement has a very important role in state implementation, especially in emerging clean state and free from corruption, collusion, and nepotism. The existed management is very fragmented and is not proper enough in handling the emerged problems in the process of Good and Service procurement, so that consolidation is necessary for various regulation in the form of legislation which manage the procurement, as one of the efforts to increase healthy transparency and competition. Besides, the regulation for the procurement, in the case of fulfilling the void law in several things related to the procurement, there is law clarity and certainty toward the procurement process, so that it does not make the executor in the site worry about implementation that is not suitable with the procedure, which can lead to prosecution of criminal law in the future, Therefore, the centered policy, informative notification, transparency in the procedure and mechanism process of the procurement, and incentive monitoring in every level through an institution that is permanently organizes and manages the procurement implementation process are needed. This institution functions continuously to conduct assessment, renewal, development, and arrangement various policy in the term of good and service procurement, and monitoring, including human resource development aspect, system development of the procurement, and society participation